The restless mind while driving: drivers' thoughts behind the wheel. (March 2015) - Berthié, Gaëlle; Lemercier, Céline; Paubel, Pierre-Vincent; Cour, Maurice; Fort, Alexandra; Galéra, Cédric; Lagarde, Emmanuel; Gabaude, Catherine; Maury, Bertrand
Highlights: The originality of our work is to investigate mind wandering in a real-car driving context. Mind-wandering had a mental cost and occurred especially during professional and well-known trips, including highways or motor by-pass. Thoughts were predominantly related to present and future oriented contents, involving a neutral emotional valence and private concerns. Even if drivers reported noticing degradation of their driving behavior when they were inattentive, they did not consider them as critical. Theoretical and methodological implications for driving safety of present research are discussed. Abstract: Recent research has clearly shown that inattention when driving has an indisputable impact on road safety. " Mind wandering " (MW), an inattentional state caused by a shift in attention from the ongoing task to inner thoughts, is not only frequent in everyday activities but also known to impact performance. There is a growing body of research investigating the concept of MW, suggesting potential causes that could foster such a phenomenon. Only one epidemiological study has focused on this issue in a critical driving context (Galéra et al., 2012 ), and it revealed the harmful effects of MW in increasing the risk of a car crash. Experimental studies rather consider that driver would adduce in MW (Lemercier et al., 2014 ). When the driving context is too hard or the thought too difficult to proceed, driver reduced their MW. The aim of this paper is to examine this issue using the most recent trip of ordinary drivers whose MW state did not lead to a road accident. Using a questionnaire, information was collected about the participants' most recent trip as a driver, including: (1) personal characteristics, (2) context in which MW occurs, (3) awareness of MW episodes and finally (4) characteristics of the thoughts. Results: revealed that MW affected 85.2% of the drivers, who spent on average 34.74% of their trip in a MW state. Moreover, we found that the contexts which favor MW are situations in which less of the driver's attention is needed to drive, such as familiar commutes, monotonous motorways or by-passes, or when drivers were alone in their cars. In these MW situations, the drivers quickly became aware of their MW episodes. Thoughts tend to involve neutral private concerns, related to present- or future-oriented content. Our findings suggest that MW is a functional state aiming to solve current problems. Future investigations should focus on this critical concept of MW when driving, both to identify safety issues and to provide suitable solutions for drivers subject to a wandering mind.